CONTENTS VALIDITY OF BATTERY CONSTRUCTION PENCAK SILAT PHYSICAL TEST IN EARLY AGE (10-12 YEARS) - Nurhidayah, Dewi (MEDIKORA, 2024)
Evaluation is an important thing in the training process. To carry out an evaluation, good instruments are needed that are to the sport’s specifications. Instruments for measuring training results for early-age martial artists have not yet been developed. Thus, this research aims to compile and test the content validity of the physical test battery for early childhood pencak silat. This research is a quantitative descriptive study with survey techniques using the Delphi method. The subjects in this research are two physical conditioning experts, two pencak silat experts, one child development expert, and two pencak silat trainers. he data collection technique in this research used the Delphi technique. The content validation test used the Aiken V formula with the help of 7 experts consisting of 2 physical condition experts, 2 pencak silat experts, 1 child development expert, and 2 pencak silat trainers. The results show flexibility using sit and rich has a validity value of 1, speed using the 30-meter sprint has a validity value of 1, strength using push-ups has a validity value of 0.95, sit-ups have a validity value of 1, and wall sits a validity value of 1, agility using the shuttle run has a validity value of 0.95, and aerobic endurance using the beep test has a validity value of 0.76.The overall content validity of the test instrument is 0.9. Thus, it can be concluded that the physical test battery for early childhood pencak silat has high content validity. The reliability and norms of the early-age pencak silat physical test battery have not been tested. So it is important to test the instrument’s reliability and prepare physical test norms for early-age pencak silat in future research.